Serial Ultrasound and Computed Tomography Findings of Torsion of Lipomatous Appendage of the Falciform Ligament in a Child Treated by Conservative Management - Nam, Jeong Gu; Choi, Seong Hoon; Kang, Byeong Seong; Kim, Jae Yeong; Kwon, Woon Jung (Journal of the Korean Society of Radiology, 2015)
Torsion of the lipomatous appendage of the falciform ligament is extremely rare, and most patients have previously been treated surgically. We reported a case of torsion of the lipomatous appendage of the falciform ligament in a child, diagnosed by ultrasound (US) and computed tomography (CT) and treated conservatively. Real-time US and CT can aid an accurate diagnosis, and follow-up US can aid in making appropriate decisions for conservative treatment. KCI Citation Count: 0